Potential resuscitative endovascular balloon occlusion of aorta candidates: defining the potential need using the National Trauma Registry. Issue 4 (27th April 2020) - Daskal, Yaakov; Hershkovitz, Yehuda; Peleg, Kobi; Dubose, Joseph J.; Kessel, Boris; Jeroukhimov, Igor; Givon, Adi; Dudkiewicz, Mickey; ,
Abstract: Background: Most of the trauma patients who die in the first 24 h from arrival to the hospital do so as a result of haemorrhagic shock. Resuscitative endovascular balloon occlusion of the aorta (REBOA) facilitates expedient proximal aortic control, potentially bridging a needed gap for partial or non‐responders to traditional resuscitation en route to emergent definitive haemostasis. This resuscitation tool continues to evolve and has recently achieved some consensus defined indications for its use. The aim of this study is designed to examine the potential utility of REBOA among trauma victims who die within 24 h of arrival. Methods: Data of all trauma patients who died in the first 24 h, from 2012 to 2017 were extracted from the National Trauma Registry in the Gertner Institute for Epidemiology and Health Policy Research. Patients who died in the first half an hour, and those with neck and thorax injuries were excluded. Demographics, clinical and injury data were collected. Results: Overall, 129 patients were included; 74% male and 26% female with the mean age of 46.4 years. A total of 76% suffered blunt trauma and 24% penetrating trauma. Mean survival time was 5.87 h. The cause of death was major abdominal organ injury in 47.2%, injury to major abdominal vessel in 23.3% and pelvic fractures in 21.7%. A total of 69 patients (53.5%) ultimately required delayed resuscitative thoracotomy in the operation room. Conclusion: Registry data suggest that there is a subset of patients presenting to modern trauma centres who might benefit from REBOA in order to avoid death. Abstract : The aim of this study was to examine the potential utility of resuscitative endovascular balloon occlusion of aorta among trauma victims who die within 24 h of arrival due to haemorrhage.